Policing football crowds in Sweden. Issue 1 (2nd January 2019) - Stott, Clifford; Havelund, Jonas; Williams, Neil
ABSTRACT: The policing of football crowds in Sweden is underpinned by a national coordination approach based upon a set of conflict reducing principles and supported by crowd theory. The approach is referred to as the Special Police Tactic (SPT). While focused on police capacity to exercise force, the SPT also gives primacy to tactics based upon communication, in the form of Dialogue Police. Existing research on the SPT focuses exclusively on the policing of protest crowds. This paper extends the existing literature by reporting on a large scale three-year observational research project examining the SPT as it is applied to football fixtures involving several of Sweden's major football clubs. On the basis of our analysis we draw out how policing operations in line with facilitation and communication were associated with effective outcomes. However, we also highlight deficiencies in national coordination and coherence as well as highlighting important innovations with regard to approaches to dialogue with football fans. We explore the implications of our analysis for theoretical understanding of effective football crowd management and engagement with fan culture.